Efeito do tipo de ordenha e ambiente sobre a qualidade do leite cru com base na contagem de células somáticas na mesorregião do Sul Goiano - Silva, Juliana Cassiano (2015)
The objective was to evaluate the effect of the type of milking and the environment in the quality of raw milk by identification the Somatic Cell Count - CCS in samples obtained from farms in the mesoregion of south goiano and correlate it with the different types of milk, and the milk components: fat, protein, lactose and total solids (ST). Furthermore, we sought to diagnose the prevalence of subclinical mastitis by CCS, evaluate the correlation between CCS and milking type with antimicrobial residues, and check the influence of season, temperature and humidity index (THI) and Equivalent Temperature Index (ITE) on the CCS. The research developed in farms with different types of milking, being divided into manual and mechanical milking. The datas were collected from January 2011 to December 2013, and in each property was collected a monthly sample in the expansion tank, a total of 8242 samples, which were later sent for analysis. The diagnosis of the milk quality held by electronic count of somatic cells, for the FossomaticTM® and the levels of the components were analyzed using the MilkoscanTM FT®, the detection of antibiotic residues was performed using the Delvotest-P and meteorological data were obtained from the National Institute of Meteorology - INMET in Catalão-GO station. Among the variables type of it milks and subclinical mastitis, there was dependent relationship (p <0.05). The milking mechanics was the one with a higher prevalence of subclinical mastitis with 58% (910) of the samples presented CCS> 300.000 cells/mL. Among the variables type of milking and CCS advocated by Instruction n°62/2011 (BRASIL, 2011), there was a significant relationship (p <0.05). Only 19,53% (1610) of the samples had CCS > 500.000 cells/mL. According to the statistical analysis, there was a positive correlation between CCS and fat and ST, however, there was a negative correlation between the CCS and the protein and lactose contents. The type of milking and the somatic cell count did not affect the presence or absence of antimicrobial residues. During the rainy season has become a CCS elevation compared to the dry season, but there was no correlation between CCS and environmental indices (ITE and ITU). Regarding environmental indices can be seen that with the increase of the ITU occurred a decrease in fat and an increase in ST and lactose. It can be concluded that the type of manual milking showed the lowest prevalence of subclinical mastitis in relation to milking and with elevated CCS is a reduction in the concentrations of protein and lactose and an increase in fat and total solids in the raw milk.